1999
DOI: 10.1002/(sici)1097-4628(19990509)72:6<849::aid-app10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy networks toughened by core-Shell particles: Influence of the particle structure and size on the rheological and mechanical properties

Abstract: The core-shell particles considered were poly(butyl acrylate) core/epoxy groups functionalizing the poly(methyl methacrylate) shell. Physical and thermomechanical properties of benzyl dimethylamine (BDMA)-catalyzed diglycidyl ether of bisphenol A (DGEBA)/dicyandiamine epoxy networks toughened with core-shell particles were studied. The blends were prepared under well-defined processing conditions. The resulting properties were found to depend on the state of the dispersion of the particles in the prepolymer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Most studies on nanocomposites fillers reveal a progressive increase in modulus with increasing reinforcement volume fractions; examples of studies in polymers include claybased nanocomposites, [12][13][14]19,20 microscale ceramic TPs and needles, 15,16,21 graphene, 17,22 carbon nanotubes, 13,18,[23][24][25][26][27] carbon black, 3,8,10,19,20,22,[28][29][30][31] glass fibers, 3,8,10,21,32-34 and others. 22,[35][36][37] This clearly is to be expected from a rule of mixtures analysis 4,7,13,[23][24][25][26][27] owing to the much higher Young's modulus of the filler.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies on nanocomposites fillers reveal a progressive increase in modulus with increasing reinforcement volume fractions; examples of studies in polymers include claybased nanocomposites, [12][13][14]19,20 microscale ceramic TPs and needles, 15,16,21 graphene, 17,22 carbon nanotubes, 13,18,[23][24][25][26][27] carbon black, 3,8,10,19,20,22,[28][29][30][31] glass fibers, 3,8,10,21,32-34 and others. 22,[35][36][37] This clearly is to be expected from a rule of mixtures analysis 4,7,13,[23][24][25][26][27] owing to the much higher Young's modulus of the filler.…”
Section: Introductionmentioning
confidence: 99%
“…22,[35][36][37] This clearly is to be expected from a rule of mixtures analysis 4,7,13,[23][24][25][26][27] owing to the much higher Young's modulus of the filler. 1,3,5,8,10,22,[28][29][30][31] Fewer studies have shown the opposite effect, that of a reduction in Young's modulus. 3,8,10,12,14,[32][33][34] For example, it has been reported for bio-inspired nano-cellulose-rubber composite materials where the Young's modulus decreased by forty times through exposure to small chemical moieties that regulated nanofiller-polymer interaction, 2,6,[35][36][37] in silicon cantilevers in which the Young's modulus decreased monotonically by three times with cantilever thickness, 4,7 and in pure polymers and metallic thin films where a two to five times stiffness decrease was seen due to humidity 1,5 and temperature; 12 additionally a thirtyfold decrease in hardness has been reported by introducing acid or small oligomers into a polymer matrix to disrupt interchain bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggests that the core shell particles are absorbing and redirecting the impact and crack propagation through deformation, debonding, and cavitation in the matrix. These effects have been studied by scanning electron microscopy, atomic force microscopy, and simulation in related literature [28][29][30][31][32]. Prasad and Grubb present the frequency shift per unit stress, a calibration for assessing the Raman spectroscopic shifts, as dṽ=dr ¼ À2:44 cm À1 per GPa [26].…”
Section: Discussionmentioning
confidence: 99%
“…Also, PLA/PBAT blends showed higher elongation at break than pure PLA. Bécu-Longuet et al [34] studied the effect of functionalized core-shell particles with different sizes and surface functionalities on the toughening of epoxy resin. They showed that the Young's modulus of the epoxy resin decreased slightly in the presence of functionalized core-shell particles.…”
mentioning
confidence: 99%